Essential Reading In Contemporary Waqf Issues - Dr. Monzer Kahf (CERT Publication, 2011)
A review of this history show that the nation of charitable endowments had long been realized even before the advent of islam. waqf, through the eyes of isla, is seen as a catalyst for the scientific.